Performance assessment and change in the academic profession in Portugal - Stoleroff, A. D. (2018)
The introduction of a performance assessment model based upon the measurement of merit through explicit, standardized,and objective criteria of productivity has provoked significant changes in the academic profession within the public higher education in Portugal. Given that employment security was made con-tingent upon obtaining adequatepositive scores and promotion upon achieving max-imum scores, a new institutional culture framed by precariousness and competitionseems to have emerged. Moreover, asa consequence of austerity and with itthe freezing of the pay awards associated with a promotion, the positive effects of ex-cellent performance have been suppressed, while punitive measures for inadequate performance have been maintained. Based on ongoing qualitative research consisting of analysis of union position statements, interviews with union representatives,and interviews with academic staff of a Portuguese higher education institution, this article advances the hypothesis that evolutionhas taken place from resistance to routinization and acceptance of assessment procedures.